Ligand engineering of immobilized nanoclusters on surfaces: ligand exchange reactions with supported Au11(PPh3)7Br3. Issue 24 (22nd April 2020) - Truttmann, Vera; Herzig, Christopher; Illes, Ivonne; Limbeck, Andreas; Pittenauer, Ernst; Stöger-Pollach, Michael; Allmaier, Günter; Bürgi, Thomas; Barrabés, Noelia; Rupprechter, Günther
Abstract : Ligand exchange on Au nanoclusters has been proven to be a powerful tool for tuning their properties, but has so far been limited to dissolved clusters in solution. Within this work, ligand exchange has been extended to supported Au11 nanoclusters. Abstract : The properties of gold nanoclusters, apart from being size-dependent, are strongly related to the nature of the protecting ligand. Ligand exchange on Au nanoclusters has been proven to be a powerful tool for tuning their properties, but has so far been limited to dissolved clusters in solution. By supporting the clusters previously functionalized in solution, it is uncertain that the functionality is still accessible once the cluster is on the surface. This may be overcome by introducing the desired functionality by ligand exchange after the cluster deposition on the support material. We herein report the first successful ligand exchange on supported (immobilized) Au11 nanoclusters. Dropcast films of Au11 (PPh3 )7 Br3 on planar oxide surfaces were shown to react with thiol ligands, resulting in clusters with a mixed ligand shell, with both phosphines and thiolates being present. Laser ablation inductively coupled plasma mass spectrometry and infrared spectroscopy confirmed that the exchange just takes place on the cluster dropcast. Contrary to systems in solution, the size of the clusters did not increase during ligand exchange. Different structures/compounds were formed depending on the nature of the incoming ligand. The feasibility to extend ligand engineering to supported nanoclusters is proven and it may allow controlled nanocluster functionalization.